Cellular response markers and cytokine gene expression in the central nervous system of cattle naturally infected with bovine herpesvirus 5 - Cardoso, T. C. [UNESP]; Ferreira, H. L.; Okamura, L. H. [UNESP]; Giroto, T. P. [UNESP]; Oliveira, B. R. S. M. [UNESP]; Fabri, C. U. F. [UNESP]; Gameiro, R. [UNESP]; Flores, E. F. (Elsevier B.V., 2016)
The present study reports an investigation on the phenotype of inflammatory and immune cells, cytokine and viral gene expression in the brains of cattle naturally infected with bovine herpesvirus 5 (BHV5). Brain sections of 38 affected animals were analysed for the nature and extent of perivascular cuffs in the Virchow-Robin space and parenchyma. Histopathological changes were severe in the olfactory bulbs (Obs), hippocampus, piriform, frontal, temporal and parietal cortices/lobes and were characterized by inflammatory infiltrates in Virchow-Robin spaces. The histopathological changes correlated positively with the distribution of BHV5 antigens (r=0.947; P < 0.005). Cells of CD3+ phenotype were predominant in areas with severe perivascular cuffs. Viral antigens and genomic viral DNA were detected in the Obs and piriform lobe, simultaneously (r = 0.987; P < 0.005). Similarly, pro-inflammatory cytokine genes INFG, IL2, TNF and LTBR were expressed in the same brain areas (P < 0.005). These results provide important information on the inflammatory and immunological events accompanying BHV5 neurological infections. Our findings provide the first evidence for increased immune activation followed by inflammatory cytokine expression, positively correlated with viral replication in the cranial areas of the brain. Taken together, these results suggest that the host immune response and inflammation play a crucial role in the pathogenesis of acute encephalitis by BHV5 in cattle. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Cattle; Inflammatory response; Viral meningoencephalitis